Antifungal potential of blends of specific essential oils against Tinea capitis and Tinea corporis - Singh, Avinash; Kumar, Ajay (International Journal of Scientific Research in Biological Sciences, 2018)
Since ancient times, folk medicines have advantageous from the use of natural products and plant derivatives, such as essential oils, to inhibited different types of diseases. In Nature, essential oils play an important role in protecting the different types of infections on human beings. Combinations of different essential oils are often an option for therapeutic use for human health. Several researchers have examined in detail the modes of action of essential oils and most of their components and combinations. Approximately 90 types of essential oils with more than thousand combinations can be identified as being suggested for dermatological use. This research explores the antifungal properties of essential oils as natural treatment against pathogens responsible for dermatological infections. The purpose of this research is to describe the properties of essential oils, principally as antifungal agents, and their role in the form of combinations.